Optimization Analysis of Supply Chain Resource Allocation in Customized Online Shopping Service Mode. (4th May 2015) - Yao, Jianming; Gu, Mengjie
Abstract : For an online-shopping company, whether it can provide its customers with customized service is the key to enhance its customers' experience value and its own competence. A good customized service requires effective integration and reasonable allocation of the company's supply chain resources running in the background. Based on the analysis of the allocation of supply chain resources in the customized online shopping service mode and its operational characteristics, this paper puts forward an optimization model for the resource allocation and builds an improved ant algorithm to solve it. Finally, the effectiveness and feasibility of the optimization method and algorithm are demonstrated by a numerical simulation. This paper finds that the special online shopping environments lead to many dynamic and uncertain characters of the service demands. Different customized service patterns and their combination patterns should match with different supply chain resource allocations. The optimization model not only reflects the required service cost and delivery time in the objective function, but also considers the service scale effect optimization and the relations of integration benefits and risks. The improved ant algorithm has obvious advantages in flexibly balancing the multiobjective optimizations, adjusting the convergence speed, and adjusting the operation parameters.